(untitled) (Bangladesh Journal of Medical Education, 2021)
The reported illnesses and injuries attributed to environmental and occupational factors is a major health challenge being experienced globally over the years.1 In current decade, Bangladesh has experienced a number of environmental and occupational health-related hazards that not only have cost huge government involvement, medically and financially but also caused international bodies to intervene into local affairs (see Table 1). These unprecedented events often question how prepared are young Bangladeshi doctors if they are to receive and manage disaster-victims at real time.2 Globally, ‘Occupational and Environmental Medicine (OEM)’ subject is lectured at third-year of the MBBS course during ‘Population Health’ or ‘Community Medicine’ rotation. Efficient, effective and enjoyable learning on OEM-topics can equip future doctors with important basic knowledge and required practical skills that are necessary to manage cases/victims from pandemic, work-hazards or disasters. Students’ positive engagement with OEM may raise their interest with specialist careers in Community Medicine (Com-Med). Some developed-country studies3-7 reported that students who went through problem-based-learning (PBL) tutored classes made better academic performance on Preventive Medicine, Public Health and Community Health topics than those who had experienced traditionally lecture-tutored curriculum. An Indian study done by Joseph et al.8 documented similar findings. The purpose of this review paper is to appraise current OEM-syllabus under the Com-Med curriculum in Bangladesh and scope, whether the PBLs or case-based-learning (CBLs) model could be appropriate if applied through ‘blended-learning’ or, ‘flipped-classroom (backed by audio-video supports)’ format. This literature-evidenced, student-centred teaching model expectedly would improve students’ practically-oriented learning via their in-class working over real-life cases/problems. Ideally, these cases would be constructed by content-experts and delivered initially by guest-lecturers. Bangladesh Journal of Medical Education Vol.12(1) 2021: 50-67